Optimization design of optical windows for deep-sea pressure-resistant structures based on transition materials - Wei, Yucong; Ma, Guoliang; Zhang, Hailong; Zhang, Xiaowei; Quan, Xiangqian (Frontiers in Marine Science, 2023)
Introduction The design of high-pressure optical windows is one of the key tasks in deep-sea exploration, as it directly determines the reliability and maximum operating depth of underwater optical equipment. Method In this paper, mechanical modeling and finite element analysis methods are employed to study optical windows. Results and discussion Results show that changes in boundary conditions during loading significantly affect the stress distribution of the window. Based on this conclusion, an optimization design method is proposed, which involves the use of transition materials to reduce the impact of base deformation on the window. The study further analyzes the effects of the transition material’s Young’s modulus, Poisson’s ratio, thickness, and friction coefficient on the stress of the optical window. A calculation method for material selection criteria is proposed to select appropriate transition materials, and actual materials are used for verification. Finally, the reliability of the optimization design scheme based on transition materials is confirmed through high-pressure experiments.